Improvement of boiling process in fish cracker production - Mohamad Nafis, Jamaluddin (2013)
Boiling process is performed at the final stage in fish cracker processing. Long process time of boiling create bottleneck that limits daily production of fish cracker. Traditionally, the heat is produce to boil water is by burning fire woods. The invention of diesel-fired boiler has improved the process but still there are some problem occurs at the station. Therefore, a new boiler is designed to improve the boiling process by using LPG burner which has 2.9 % higher calorific value than diesel. The boiler designed must be simulated to study the heat convection inside the boiler by using SolidWorks Flow Simulation to see the temperature distribution inside the new boiler. Multiple layers bottom plate of the boiler consist of an aluminium plate sandwiched between two stainless steel plates is used to increase the rate of heat transfer from the flame into the water inside the boiler. The result from the simulation proves that the multiple layers bottom plate of the boiler has a higher rate of heat transfer than the single layer plate where the time taken for water to boil is 42.2 % shorter than the single stainless steel layer bottom plate boiler.